Negosiasi Identitas Budaya melalui Musik Ritual Masyarakat Pesisir Jawa - Kadek Anggara Rismandika (Mahāsarā, 2026)
This study aims to examine the negotiation of cultural identity through ritual music practices among coastal communities in Java. Ritual music in coastal societies functions not merely as ceremonial accompaniment but as a symbolic medium through which collective identity is expressed, contested, and reconstructed in everyday social life. This research employs a qualitative ethnographic approach conducted in a coastal village in Java, involving ritual performers, community elders, religious figures, and local residents across generations as participants. Data were collected through participant observation during the preparation and performance of the ritual, in-depth interviews, and audio-visual documentation supported by detailed fieldnotes. Credibility was strengthened through source and technique triangulation and member checking with key informants. Data analysis was conducted thematically using an interactive cycle of data reduction, data display, and conclusion drawing. The findings reveal that ritual music serves as a dynamic arena for negotiating identity between tradition and modernity, local belief systems and formal religious influences, as well as communal heritage and external cultural pressures. Musical elements such as repertoire selection, instrumentation, performance structure, and spatial arrangement reflect adaptive strategies that maintain continuity while accommodating socio-cultural change. The study also identifies generational differences in interpreting ritual music, indicating an ongoing reinterpretation of cultural symbols through discourse and participation. This research concludes that ritual music in Javanese coastal communities operates as an active cultural mechanism that sustains collective identity while enabling flexible adaptation to contemporary transformations. The findings offer empirical grounding for ethnomusicological discussions on ritual, identity, and change and provide practical insight for community-based cultural safeguarding.